Predictive factors and prognosis for recurrent laryngeal nerve invasion in papillary thyroid carcinoma - Chen, Wenjie (Onco Targets Ther, 2017)
BACKGROUND: Recurrent laryngeal nerve (RLN) invasion in papillary thyroid carcinoma (PTC) is one of the main predictors of poor prognosis. The present study investigated the risk factors for RLN invasion in PTC patients. METHODS: A total of 3,236 patients who received thyroidectomy due to PTC in Thyroid and Parathyroid Surgery Center of West China Hospital of Sichuan University were reviewed. Demographics and clinical factors, imaging examination (ultrasonography) characteristics, surgical details, postoperative pathological details, recurrence, and postoperative complications were recorded. Univariate and multivariate analyses were used to study the risk factors of RLN invasion, Kaplan–Meier method was performed to compare the outcomes of tumor recurrence. RESULTS: Patients with RLN invasion had a higher recurrence rate than those in the control group (p<0.001). Multivariate analyses showed that age greater than 45 years (p<0.001), a largest tumor size bigger than 10 mm (p<0.001), clinical lymph node metastasis (cN1) (p<0.001), posterior focus (p<0.001), extrathyroidal extension (p<0.001), esophageal extension (p<0.001), tracheal extension (p<0.001), and preoperative vocal cord paralysis (p<0.001) were independent predictors for RLN invasion. CONCLUSION: PTC patients with RLN invasion have a negative prognosis and a higher recurrence rate. Meticulous operation and careful follow-up of patients with the above factors is recommended.